F: Implementasi Manajemen Strategi Rumah Sakit Dalam Meningkatkan Mutu Pelayanan dan Kinerja Organisasi: Literature Review - Ari Yulianto; Hayuningtiyas Purbashinta; Desma Elvita; Radina Ni Nyoman Rusmiati; Asnet Leo Bunga (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
ABSTRACTBackground: Hospitals operate in an increasingly competitive environment that demands continuous improvement of service quality, patient safety, efficiency, and organizational performance. Strategic management, comprising strategy formulation, implementation, and evaluation, is a key determinant of hospital sustainability. However, the implementation stage remains the most challenging, as many well-formulated strategies fail to be translated into measurable performance. Purpose: To review scientific evidence regarding the implementation of hospital strategic management and its role in improving service quality and organizational performance. Method: A literature review using a systematic approach based on PRISMA guidelines. Literature searches were conducted through PubMed, ScienceDirect, Google Scholar, and Garuda databases for articles published between 2020 and 2026. Eight articles met the inclusion criteria and were included in the analysis. Results: The success of hospital strategic management implementation was determined by the interaction of strategic planning and environmental analysis (SWOT and PESTEL), performance measurement systems (the Balanced Scorecard and key performance indicators), strategic leadership and organizational culture, adequate organizational structure and resource allocation, and the use of hospital management information systems. These factors collectively contributed to improved service quality, patient safety, operational efficiency, and cost control. Conclusion: Hospital strategic management implementation is a multidimensional process influenced by the alignment of leadership, planning, performance measurement, organizational systems, and information technology. Hospitals should strengthen strategic leadership, structured strategic planning with measurable indicators, and supportive organizational systems to improve service quality and organizational performance.Keywords: hospital; lmplementation; organizational performance; service quality; strategic management